2004
DOI: 10.1080/01459740490448911
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Constructions of Sexual Violence as Told by Female Rape Survivors in Three Populations of the Southwestern United States: Scripts of Coercion, Scripts of Consent

Abstract: There is a growing literature on the narrative construction of rape as sexual violence. This is puzzling, since, in certain contexts, violence may stifle narrative production. Researchers of atrocities, for example, propose that the experience of recurring terror disrupts narrative cohesion in reporting lived trauma. Genocidal horror occurs in the context of communities and ethnic groups. Our rape survival data from women of three populations in the southwestern United States reflect traumas of sexual violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…For example, it has been theorized, and some research supports, that Latina women may hold more "stereotypical" (e.g., a violent, stranger assault) rape scripts than European American women (Littleton et al 2007a). This could be because Latina women are less likely to be a recipient of a victim's disclosure than European American women (Bletzer and Koss 2004;Ramos-Lira et al 1999), and thus may have less well-elaborated rape scripts (e.g., relying on media depictions of rapes). In addition, Latinas tend to hold more traditional gender role attitudes (Kane 2000) than European Americans, which has been associated with adherence to stereotypical beliefs about rape (Muehlenhard and MacNaughton 1988).…”
Section: Introductionmentioning
confidence: 95%
“…For example, it has been theorized, and some research supports, that Latina women may hold more "stereotypical" (e.g., a violent, stranger assault) rape scripts than European American women (Littleton et al 2007a). This could be because Latina women are less likely to be a recipient of a victim's disclosure than European American women (Bletzer and Koss 2004;Ramos-Lira et al 1999), and thus may have less well-elaborated rape scripts (e.g., relying on media depictions of rapes). In addition, Latinas tend to hold more traditional gender role attitudes (Kane 2000) than European Americans, which has been associated with adherence to stereotypical beliefs about rape (Muehlenhard and MacNaughton 1988).…”
Section: Introductionmentioning
confidence: 95%
“…Latinas may be less likely than European Americans to know someone who was raped because Latina victims appear to be even less comfortable than women of other ethnic groups disclosing a rape experience. Indeed, focus group research has shown that Latina women often are uncomfortable discussing the topic of rape and are less likely than European Americans to provide to others a detailed description of rape in general or of their own rape experience in particular (Bletzer & Koss, 2004;RamosLira, Koss, & Russo, 1999). Thus, even if Latinas have had someone disclose a rape experience to them, the disclosure may have been vague and lacking in detail.…”
mentioning
confidence: 96%
“…Previous studies (e.g., Bletzer & Koss, 2004), have found that Latina women are uncomfortable discussing the topic of rape and are less likely than European Americans to disclose rape experiences. Based on the cultural value of women's chastity, discussing rape could be difficult for Latinas, particular when disclosing to a therapist from the same culture.…”
Section: Discussionmentioning
confidence: 97%